2016
DOI: 10.1002/pbc.26162
|View full text |Cite
|
Sign up to set email alerts
|

Prospective study of neuropathic pain after definitive surgery for extremity osteosarcoma in a pediatric population

Abstract: Background Neuropathic pain (NP) after definitive surgery for extremity osteosarcoma (OS) has not been previously characterized. This study prospectively investigates the incidence, duration, and treatment of NP in limb sparing surgery and amputation groups. Procedure In patients treated for OS on a chemotherapy and definitive surgery (limb sparing vs. amputation) protocol (OS08), we prospectively collected the following data: (i) demographical data (age, sex, race); (ii) NP time of onset and duration; and (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 28 publications
2
35
0
Order By: Relevance
“…Anghelescu et al found that the mean duration of postoperative neuropathic pain was 6.5 weeks after surgery for patients with extremity osteosarcoma, which could explain continued opioid use over time in our patients. 14 Our study did not investigate phantom limb pain; nevertheless, a previous study showed great improvement in outcomes of amputees with phantom limb pain, with little recurrence after 1 year of surgery. 15 The role of amputation in pediatric patients with metastatic osteosarcoma in our study correlates well with positive findings from several studies on adults with osteosarcoma and/or other bone tumors.…”
Section: Discussionmentioning
confidence: 80%
“…Anghelescu et al found that the mean duration of postoperative neuropathic pain was 6.5 weeks after surgery for patients with extremity osteosarcoma, which could explain continued opioid use over time in our patients. 14 Our study did not investigate phantom limb pain; nevertheless, a previous study showed great improvement in outcomes of amputees with phantom limb pain, with little recurrence after 1 year of surgery. 15 The role of amputation in pediatric patients with metastatic osteosarcoma in our study correlates well with positive findings from several studies on adults with osteosarcoma and/or other bone tumors.…”
Section: Discussionmentioning
confidence: 80%
“…Although this somewhat‐conservative strategy reflected the most common clinical practice, there are reports of substantially higher doses of gabapentin, at 45 mg/kg per day in a case report (n = 2) and 43.8 mg/kg per day in a prospective study of postsurgical neuropathic pain after surgery for osteosarcoma treatment (n = 30) (Table 3). 24,25 Although our study design indicated a gabapentin regimen of 20 mg/kg per day, the actual doses taken were lower (mean 18 mg/kg per day), most likely due to missed doses secondary to some combination of lack of adherence, concurrent nausea/vomiting related to other chemotherapy, or nil per os status related to anticipated anesthetics for oncological or surgical procedures. Comparisons of regimens for NP treatment with gabapentin in adults and children 23 support the concept that underdosing strategies are common in pediatric populations, whereas the standard recommendation for adults is to escalate doses up to 300 mg/day or 50‐70 mg/kg per day.…”
Section: Discussionmentioning
confidence: 94%
“…burning or hot, electric shocks or shooting, pricking or pins and needles) suggest possible neuropathic pain [4]. Similar sensations have been reported by children 6 years and older, including burning, tingling, numbness, itching, pins and needles [20][21][22], but the reporting and validity of different descriptors is also dependent on each individual's verbal repertoire [23]. The McGill Short-Form questionnaire, which includes sensory and affective adjectives, has identified group differences in adults with neuropathic and non-neuropathic pain [9], and tender, sharp, burning, stabbing and shooting were frequently reported by 10À17 year old adolescents with neuropathic pain (Fig.…”
Section: Sensory Descriptorsmentioning
confidence: 88%